Efektifitas Pendidikan Kesehatan Tentang Bahaya Minuman Keras pada Remaja dengan Metode FGD dan Snowball Throwing - Marsito Marsito; Juneth Anandhita (STIKes Payung Negeri Pekanbaru, 2020)
The prevalence of alcoholic beverage consumption among adolescents is increasing. The results of a preliminary study in Kalibangkang Village many teenagers consume liquor and the results of interviews in MTs SA Kalibangkang found students do not know the dangers of liquor. This study aimed to determine the effectiveness of health education about the dangers of alcoholism in adolescents with the method of focus group discussions and snowball throwing at MTs SA Kalibangkang. This study used a quasi-experimental method with the type of approach used is pre-test and post-test with control group design. The research sample of 86 respondents were taken by random sampling techniques. The instrument used to collect data was a 12 item knowledge questionnaire. Data analysis used Wilcoxon and Mann-Whitney tests. The results showed there was an influence of the focus group discussion method in increasing knowledge about the dangers of liquor (p = 0.000), there was an influence of the snowball throwing method in increasing knowledge about the dangers of liquor (p = 0,000) and there were no significant differences between the methods focus group discussion and snowball throwing in increasing knowledge (p = 0.481). The conclusion of this study is the method of focus group discussion and snowball throwing is an effective method to increase knowledge about the dangers of drinking alcohol in adolescents. The next researcher is expected to research about health education in adolescents by comparing health education methods with other methods.